KETAHANAN PANGAN PADA RUMAH TANGGA MISKIN DI DAERAH RAWAN BANJIR KOTA SURAKARTA - Riptanti, Erlyna Wida; Rahayu, Wiwit; Sundari, Mei Tri (Caraka Tani: Journal of Sustainable Agriculture, 2011)
Condition of impecunious household food security will progressively susceptible if impecunious household live in area of disaster gristle for example floods disaster. This research aims are to identify the condition of economic social and impecunious household food security in floods gristle area. Research conducted in area of gristle of floods of Town Surakarta cover the Joyontakan, Semanggi, Sangkrah, Kampung Sewu, Jagalan, and Pucangsawit research method used analytical descriptive method. Data of food security condition taken with the interview use the questionnaire from 15 sample household to the each region. Result of research known that economic condition social of impecunious household in area of floods gristle are: a) Most storey level of education of husband and wife are finish elementary school, b) Most work lead household as labor and most of wife do not work or as housewife, c) impecunious household earnings equal to Rp. 1.294.577,77 per month which is as big of earnings come from husband, d) biggest consumption expenditure proportion is food consumption to totalizing expenditure, e) expenditure proportion consume the biggest food at vegetable group, f) expenditure proportion consume biggest non food at housing group. Impecunious household in area of flood gristle Surakarta included in a household which food insecurity.